2018
DOI: 10.1186/s40842-018-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

Rare Clinical Entity: Metastatic malignant struma ovarii diagnosed during pregnancy – Lessons for management

Abstract: BackgroundMalignant struma ovarii is an ovarian teratoma containing at least 50% thyroid tissue which has the potential to metastasize and produce thyroid hormone. Given its rarity, management strategies are not well-established. We report a case of metastatic malignant struma ovarii discovered during pregnancy with lessons for evaluation and management.Case presentationA 30-year-old woman who was two months pregnant was discovered to have struma ovarii with over half of the struma comprised of papillary thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…It was found that 25.3% (20/79) of patients were younger than 35 years at the time of diagnosis, which is in the time period of child-bearing age. There is little literature on pregnancy or fertility preservation in MSO that has been published ( 35 39 ). Even though it is extremely rare, complications in fertility preservation and management of pregnancy in metastatic MSO cannot be neglected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that 25.3% (20/79) of patients were younger than 35 years at the time of diagnosis, which is in the time period of child-bearing age. There is little literature on pregnancy or fertility preservation in MSO that has been published ( 35 39 ). Even though it is extremely rare, complications in fertility preservation and management of pregnancy in metastatic MSO cannot be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Ihalagama et al reported an uneventful pregnancy after USO, a total thyroidectomy, and RAI in a patient with non-metastatic MSO ( 35 ). Larger et al ( 39 ) and Tokuda et al ( 38 ) presented disease management in cases of accidental diagnosed with metastatic MSO after conception. The former case was treated with USO and RAI, while the latter was treated with a simple metastasis resection, but this case lacked follow-up information.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer antigen 125 is a common tumor marker for malignant struma ovarii but is of very low diagnostic value due to its nonspecificity. 10 A broad panel of immunohistochemical stains, including paired-box gene 8, thyroid transcription factor 1, and TG, can be helpful to differentiate malignant struma ovarii from other ovarian malignancies, but it has not been reported if they can help to differentiate benign vs malignant struma ovarii. 11 It remains to be seen if markers found to be useful in thyroid malignancies, such as HBME-1, specific cytokeratins (eg, cytokeratin 19), and RET, might be helpful in the diagnosis of malignant struma ovarii.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the histopathological findings of metastatic tissue very close in appearance to normal thyroid tissue and I-131 uptake within these lesions argue that the tumor remained differentiated, maintaining its capacity to concentrate I-131. 10 , 15 The presence of thyroid microcarcinoma also raises the possibility of metastasis from primary thyroid malignancy; however, the thyroid carcinoma was 3 mm in size and had clear margins with no evidence of lymphovascular invasion, making metastasis from primary thyroid cancer less likely. Moreover, 2 of 3 pathologists agreed that the lung lesions were consistent with metastatic follicular carcinoma in the context of the diagnosis of struma ovarii, with follicular lesions similar in appearance to the lung.…”
Section: Discussionmentioning
confidence: 99%
“…No existe un consenso sobre el tratamiento correcto de esta patología debido a la rareza del tumor. Existen informes que han propuesto una estadificación quirúrgica completa para el cáncer de ovario, algunos otros indican que una tiroidectomía total y iodo radiactivo pueden ayudar a la eliminación del tejido tiroideo residual después de la extirpación quirúrgica del tumor primario, así como en casos en que el tumor mida más de 2 cm, presente extensión extraovárica, metástasis a distancia, recurrencia o cáncer de tiroides primario concomitante 1,4,6,7,18,19 .…”
Section: Discussionunclassified